Q: What is the mean of 3x 3 5x-9 and 5x 12?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

5x - 10 = 3x + 2 5x - 3x = 2 + 10 2x = 12 x = 12/2 x = 6

If you mean: 5x(3x+2)-8x-7x then the expression can be simplified to 15x^2 -5x

6x - 3x = 5x - 10x + 12 6x - 3x - 5x + 10x = 12 8x = 12 8x/8 = 12/8 x = 12/8 = 3/2 x = 1.5

2x-12

5x-6+3x+128x-6+128x+6

Related questions

5x - 10 = 3x + 2 5x - 3x = 2 + 10 2x = 12 x = 12/2 x = 6

(3x + 2x) -12 =5x-12 the answer is 5x-12 it is just a simple case of simplifying

If you mean: 5x(3x+2)-8x-7x then the expression can be simplified to 15x^2 -5x

6x - 3x = 5x - 10x + 12 6x - 3x - 5x + 10x = 12 8x = 12 8x/8 = 12/8 x = 12/8 = 3/2 x = 1.5

if you mean 5x-4-3x=9 then x= 6.5

2x-12

5x-6+3x+128x-6+128x+6

If you mean: 5x(3x+2)-8x-7x then the expression can be simplified to 15x^2 -5x

Do you mean 2x²? Assuming this is the case: 2x² - 3x + 8x - 12 = 2x² + 5x - 12 = (2x - 3)(x + 4)

-5x + y = -12- 3x + 6y = -12Since both of expressions have a value of -12, their sum is - 24. This is true only whenx = 20/9 and y = -8/9.-5x + y = -12y = 5x - 12- 3x + 6y = -12-3x + 6(5x - 12) = -12-3x + 30x - 72 = -1227x = 60x = 60/27x = 20/9y = 5x - 12y = 5(20/9) - 12y = 100/9 - 12y = (100 - 108)/9y = -8/9

4x2+3x+6+5x+3x+6 = 4x2+11x+12 when simplified

2x = 5x - 12First step is to move all the like terms to one side of the equation2x (-5x) = -12-3x = -12Next, we can divide both sides by -3 to get rid of the -3 on the left side(-3x)/-3 = (-12)/-3x = 4